Ultraregular inductive limits - Jan Kucera (International Journal of Mathematics and Mathematical Sciences)
An inductive limit E=indlim En is ultraregular if it is regular and each set B⊂En, which is bounded in E, is also bounded in En. A necessary and sufficient condition for ultraregularity of E is given provided each En is an LF-space which is closed in En+1.